Performance indicators of teams at the 2003 men's World Handball Championship in Portugal - Gruic, I.; Vuleta, D.; Milanovic, D. (Kinesiology, 2006)
The research on situation-related efficiency or performance was conducted on a sample of 60 handball matches (i.e. 120 records of activities performed exclusively during attack). Twenty-four different national teams were divided into four preliminary groups of six teams. The aim of this research was to analyse the factors of situational efficiency in handball, as in the following: (1) differences in the variances of situational factors among teams and (2) the contribution of standard performance parameters to the criterion of success in handball matches defined as a goal difference in the match`s final score. The sample of predictor variables encompassed the frequencies of shot effectiveness parameters, assists and technical errors. The criterion variable was defined as the final outcome of matches. Multivariate analysis of variance was used to determine the differences that were statistically significant (p < 0.01) among the variances of the observed standard parameters of situational efficiency. Each preliminary group was observed separately. A series of regression analyses was used to define the contribution of predictor variables to the successfulness of the teams. Although the level of the contribution of separate parts of the situational efficiency varied across the groups, the statistical significance was determined in all of them on a high statistical significance level (p < 0.01) with the determination coefficients which explained the common variance of the predictor system and the criterion (a goal difference) within a range of 0.73 - 0.84. However, it was not possible to create the general model of competition efficacy, because the structure of it varied across the teams and matches.